Qualitative Analysis of Immunization Services During Covid-19 at Puskesmas Krembangan Selatan Surabaya - Esti Dwi Nastiti; Lutfi Agus Salim (Lambung Mangkurat, 2021)
Complete basic immunization coverage in Surabaya and Puskesmas Krembangan Selatan is always above 85%, however, during COVID-19, implementation of immunization at Puskesmas Krembangan Selatan has decreased. This research aims to analyze the description of the implementation of immunization during COVID-19 at Puskesmas Krembangan Selatan. This research was conducted at Puskesmas Krembangan Selatan Surabaya, from January 18 to February 26, 2021. This research was conducted using an online system, with stages coordination and interview with institution supervisor and midwife and documentation study. This research uses primary data. The results of primary data showed that during COVID-19, immunization services continued. Although there are some services that cannot be carried out. Even though there were obstacles, services are still carried out with the implementation of strict health protocols. The conclusion, during COVID-19, immunization services at the Puskesmas Krembangan Selatan were running according to health protocols, but the coverage of most immunizations had not yet reached the predetermined target because people were worried about visiting health services.